Validation of histogram‐based virtual source models for different IGRT kV‐imaging systems. Issue 9 (6th July 2020) - Boissonnat, G.; Chesneau, H.; Barat, E.; Dautremer, T.; Garcia‐Hernandez, J.‐C.; Lazaro, D.
Abstract : Purpose: Image‐guided radiotherapy (IGRT) improves tumor control but its intensive use may entrain late side effects caused by the additional imaging doses. There is a need to better quantify the additional imaging doses, so they can be integrated in the therapeutic workflow. Currently, no dedicated software enables to compute patient‐specific imaging doses on a wide range of systems and protocols. As a first step toward this objective, we propose a common methodology to model four different kV‐imaging systems used in radiotherapy (Varian's OBI, Elekta's XVI, Brainlab's ExacTrac, and Accuray's Cyberknife) using a new type of virtual source model based on Monte Carlo calculations. Methods: We first describe our method to build a simplified description of the photon output, or virtual source models (VSMs), of each imaging system. Instead of being constructed using measurement data, as it is most commonly the case, our VSM is used as the summary of the phase‐space files (PSFs) resulting from a first Monte Carlo simulation of the considered x‐ray tube. Second, the VSM is used as a photon generator for a second MC simulation in which we compute the dose. Then, the proposed VSM is thoroughly validated against standard MC simulation using PSFs on the XVI system. Last, each modeled system is compared to profiles and depth‐dose‐curve measurements performed in homogeneous phantom. Results: Comparisons between PSF‐based and VSM‐based calculations highlight that VSMs could provide equivalent dose results (within 1% of difference) than PSFs inside the imaging field‐of‐view (FOV). In contrast, VSMs tend to underestimate (for up to 20%) calculated doses outside of the imaging FOV due to the assumptions underlying the VSM construction. In addition, we showed that the use of VSMs allows reducing calculation time by at least a factor of 2.8. Indeed, for identical simulation times, statistical uncertainties on dose distributions computed using VSMs were much lower than those obtained from PSF‐based calculations. Conclusions: For each of the four imaging systems, VSMs were successfully validated against measurements in homogeneous phantoms, and are therefore ready to be used for future preclinical studies in heterogeneous or anthropomorphic phantoms. The cross system modeling methodology developed here should enable, later on, to estimate precisely and accurately patient‐specific 3D dose maps delivered during a large range of kV‐imaging procedures.